Древо: декабристы и семейство Кандинских - Бараев Владимир Владимирович (Политиздат, 1991)
Экземпляры: (20230622) / Инвентарный номер: 21215 / Цена: 3.00 / Сис.шифр: 63.3(2)521 / Авт.знак: Б 24 / ГРНТИ: 03 / ББК: 63.3(2)521-425